The Life Cycle of Entrepreneurial Ventures - Parker, Simon (International Handbook Series on Entrepreneurship,, 2007)
The Life Cycle of Entrepreneurial Ventures discusses topical issues in entrepreneurship organized around the various stages of venture creation, development and performance. The book is arranged in several parts, dealing with the pre-start stage, followed by venture creation, financing ventures, venture development, and venture performance. Each part contains several chapters written by experts in the relevant field. Like its predecessors, there are contributions from several disciplines, including economics, strategy, business, industrial organization, economic geography, finance and sociology. The multi-disciplinary flavor of the book is complemented by its international evidence base, featuring results from a range of different countries. The volume will be essential reading for everyone interested in entrepreneurship because: It contains digestible overviews of several topical issues in entrepreneurship, including nascent entrepreneurship; social (not-for-profit) entrepreneurship; formal, informal and developmental start-up capital; job creation; venture performance; and harvesting. This will help researchers and practitioners who want to cut through the information overload and distil the key points emerging from the latest academic thinking It provides new results at the cutting edge of entrepreneurship research It portrays entrepreneurship as a coherent entity by spanning the various stages of enterprise evolution.